Collaborative Processes and Collective Impact in Tourist Rural Villages-Insights from a Comparative Analysis between Argentinian and Italian Cases - Chiodo, Emilio (Sustainability.)
Multi-case-study research conducted in some rural villages of Argentina and Italy is intended to propose a model of analysis and monitoring of the "collaborative processes" which stands behind the tourist enhancement of local assets. Based on the definition of "collective impact", three main issues are analyzed: (1) the shortage of social capital, typical of some contemporary rural areas as a social problem; (2) the commitment of actors from different sectors to the common agenda of tourist development; (3) the structured form of coordination driven by extra-local organizations and programs, aimed at fostering sustainable tourism in rural villages. These issues are developed into key concepts used for the comparative description and analysis of the cases and for the definition of a common model of measurement and monitoring of the ongoing development processes. The main results are synthesized into a bidimensional plot, where the x-axis represents the "integration" dimension and the y-axis the "coordination". Each village is then represented as a point of the Cartesian plan. The final idea is to use the model to monitor the processes within each different rural village and to measure the changes over time.